“Pohulianka”: The Origin of the Name of the Western Suburb of Vilnius and the Change of Boundaries in 1790–1940 - Ambrulevičiūtė, Aelita (Lietuvos istorijos studijos, 2024)
The article examines the origin of the name “Pohulianka”, the western suburb of Vilnius, and establishes the chronology of the usage of this name from the first mentions in city plans to its disappearance from the topography of the city due to the Lithuanianization of urbanonyms in 1939–1940. Based on cartographic and written sources, the dynamics of the suburb boundaries are analyzed in the context of the changing urban name in 1790–1940.
Keywords: Pohulianka; Pohulanka; Hulanka; J. Basanavičius Street; tavern; urbanonyms; hodonyms; Vilnius suburbs; Vilnius city history